Pemanfaatan Lumpur Primer Industri Kertas sebagai Absorben - Krisna Adhitya Wardhana; Saepulloh Saepulloh; Reynaldo Biantoro (JURNAL SELULOSA, 2018)
The Utilization of Primary Sludge from Paper Mills as AbsorbentAbstractThe primary sludge from paper mill contains cellulose fiber that has high absorption capacity and potential to be used as an absorbent for hydrophobic compounds. The utilization of primary sludge from paper mill using raw material of waste paper and virgin pulp to be used as an absorbent has been conducted. The stages process of absorbent fabrication was consisted of three stages such as drying, mechanical and chemical processes. Mechanical process conducted were crushing and grinding methods to increase surface area and pore volume of sludge. Meanwhile silanization process as chemical treatment using solution of γ-metacryloxypropyl trimethoxysilane in ethanol to improve the hydrophobic properties of primary sludge was also done. Absorbent products were tested for the maximum sorbency, the sorbent performance, absorption of hydrophobic liquid, absorption of hydrophobic dust, and contact angle test to conduct their performance. The absorbency of absorbent product which is covered by cushion material was also tested. Result indicated that the absorption performance of some absorbent product is higher than commercial absorbent on hydrophobic liquid and hydrophobic dust absorption test. But it was lower than commercial absorbent on maximum sorbency and the sorbent performance test. The use of cushion material as a wrapper could make it easy in the collection and could increase the absorbency.Keywords: primary sludge; mechanical; silanization; absorbent; hydrophobic AbstrakLumpur primer dari industri kertas mengandung serat selulosa yang memiliki daya serap tinggi dan memiliki potensi dimanfaatkan sebagai absorben senyawa hidrofobik. Pemanfaatan lumpur primer industri kertas berbahan baku kertas bekas dan virgin pulp sebagai absorben telah dilakukan. Tahapan proses pembuatan absorben dari lumpur primer meliputi proses pengeringan, proses mekanis, dan proses kimia. Proses mekanis yang dilakukan adalah crushing dan grinding untuk meningkatkan luas permukaan dan volume pori-pori lumpur dilanjutkan dengan proses silanisasi (silanization) sebagai perlakuan kimia menggunakan larutan γ-metacryloxypropyl trimethoxysilane dalam etanol untuk meningkatkan sifat hidrofobik lumpur. Produk absorben diuji daya serap maksimum (maximum sorbency), kinerja absorben, penyerapan cairan hidrofobik, penyerapan debu hidrofobik, dan pengujian sudut kontak. Daya serap produk absorben yang ditutup bahan bahan cushion juga diuji. Hasil menunjukkan kemampuan absorbsi cairan hidrofobik dan debu hidrofobik dari beberapa perlakuan produk absorben lebih tinggi dari absorben komersial, sedangkan hasil maximum sorbency dan uji kinerja absorben menunjukkan hasil lebih rendah dari absorben komersial. Penggunaan bahan cushion sebagai pembungkus dapat memudahkan dalam pengumpulan dan dapat meningkatkan penyerapan.Kata kunci: lumpur primer; mekanis; silanisasi; absorben; hidrofobik